2016
DOI: 10.1242/dev.134486
|View full text |Cite
|
Sign up to set email alerts
|

The Wnt-Myb pathway suppresses KIT expression to control the timing of salivary proacinar differentiation and duct formation

Abstract: Growth factor signaling is involved in the development of various organs, but how signaling regulates organ morphogenesis and differentiation in a coordinated manner remains to be clarified. Here, we show how WNT signaling controls epithelial morphogenetic changes and differentiation using the salivary gland as a model. Experiments using genetically manipulated mice and organ cultures revealed that WNT signaling at an early stage (E12-E15) of submandibular salivary gland (SMG) development inhibits end bud morp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 35 publications
(44 citation statements)
references
References 40 publications
(47 reference statements)
2
42
0
Order By: Relevance
“…Although our data do not delineate a specific mechanism for endothelial cell signaling in controlling SMG cell fate, they are consistent with data from other embryonic organs indicating that the developing vasculature supports expansion of the primitive progenitor populations, which in turn recruits developing vasculature to the emerging epithelium. A similar premature ductal differentiation was recently reported during early development of the salivary gland that is Wnt dependent (Matsumoto et al, 2016). Similar to our data demonstrating premature ductal formation and expansion of the ductal area of the gland with compromised VEGFR2/CD31 + endothelial cell function, Matsumoto et al observed that excess Wnt signaling can induce premature ductal formation and expansion of the ductal compartment of the gland.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Although our data do not delineate a specific mechanism for endothelial cell signaling in controlling SMG cell fate, they are consistent with data from other embryonic organs indicating that the developing vasculature supports expansion of the primitive progenitor populations, which in turn recruits developing vasculature to the emerging epithelium. A similar premature ductal differentiation was recently reported during early development of the salivary gland that is Wnt dependent (Matsumoto et al, 2016). Similar to our data demonstrating premature ductal formation and expansion of the ductal area of the gland with compromised VEGFR2/CD31 + endothelial cell function, Matsumoto et al observed that excess Wnt signaling can induce premature ductal formation and expansion of the ductal compartment of the gland.…”
Section: Discussionsupporting
confidence: 92%
“…Loss of VEGFR2/CD31 + endothelial cell function would then be expected to increase canonical Wnt signaling to the epithelium, prevent proacinar differentiation, downregulate Kit expression and accelerate ductal formation. Wnt signaling is regulated by balancing activation of Wnt receptors by ligands at many levels, and several reports indicate that the Wnt family has complex roles in SMG development (Haara et al, 2011;Musselmann et al, 2011;Patel et al, 2011;Knosp et al, 2015;Maimets et al, 2016;Matsumoto et al, 2016). Thus, VEGFR2/CD31 + endothelial cells could act in many ways to modulate mesenchymal Wnt signaling to the epithelium, and might confer this regulation in a spatially restricted manner during branching morphogenesis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…By administering tamoxifen to pregnant mice at day 12.5 of gestation, Cre-mediated recombination was induced and β-catenin was stabilized in embryos at E17.5 (Matsumoto et al, 2016). Compared with Ctnnb1 (Ex3)fl/fl (control) embryos at E17.5, ppMLC, α18 and Factin in adherens junctions and podocalyxin in the apical cortices of lung epithelium were clearly observed in Ctnnb1 (Ex3)fl/fl ;Cre embryos as seen in control embryos at E14.5 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…All animal experiments were carried out according to Osaka University guidelines for the care and use of experimental animals. Tamoxifen administration in mice was performed as previously described (Matsumoto et al, 2016). Mark1 mutant mice were generated using the triple CRISPR method as previously described (Sunagawa et al, 2016).…”
Section: Micementioning
confidence: 99%